A educação em saúde bucal como estratégia para a promoção da integração ensino-serviço-comunidade em uma unidade de atenção primária à saúde do município de Fortaleza-CE - Gomes, Sória Leopoldo Lima de Alencar (2022)
This project aims to strength the teaching-service-community integration from the development of health education actions by the Oral Health Teams with a view to comprehensive care in a Primary Health Unit in the city of Fortaleza. The action research methodology was adopted with the constitution of a research group with a total of 16 people. The formation of this group is aligned with the theoretical framework of the quadrilateral of health education and thus we have representatives from the management, teaching, service, and users of the Unified Health System (SUS). The collection of empirical material was carried out through participant observation at the UAPS, conversations with key informants to obtain more information about the reality and with the execution of workshops or seminars with the research group using guiding questions for discussion. To promote the analysis of qualitative material, we use Discourse Analysis because we believe that this is the most appropriate for the analysis of our object. This research was developed within the parameters contained in resolution 466/2012 of the National Health Council since it is a research involving the participation of human beings. As a result, it was highlighted that the situational diagnosis made it possible to identify the main health needs aimed at the promotion and prevention of oral health. It was found that the elaboration and implementation of an action plan for the identified problems allowed the involvement of the different components of the quadrilateral of health education in the promotion of educational activities. The construction of lines of care for the identified groups aimed to expand care in the direction of comprehensive care. It was found that several collective health tools can help the development of educational actions and the operationalization of lines of care. It is concluded that Health Education constitutes a vector capable of bringing service and teaching closer to the socio-sanitary reality of the territories and to the health needs of the population, favoring greater integration between teaching, service and community.